Citra Perusahaan Asuransi Kredit Modal Kerja di Jawa Barat - Nasir, Amron Ahmad (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2013)
this research is aimed to analyze and to know influence significan of performance promotion program decision to working capital credit insurance company image in West Java, Indonesia.